Hubungan Kelengkapan Informasi Medis Dengan Keakuratan Kode Diagnosis Penyakit Pada Dokumen Rekam Medis Rawat Inap di RSU Universitas Muhammadiyah Malang Tahun 2024 - Suryandari, Endang Sri Dewi Hastuti; Syajidah, Almira Maryam; Zein, Eiska Rohmania (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
The completeness of medical information such as the medical assessment sheet, examination results sheet, and medical resume sheet greatly influences the accuracy of the diagnosis code. This study aims was to determine the relationship between the completeness of medical information and the accuracy of disease diagnosis codes at the Muhammadiyah University of Malang Hospital. The research’s design was a quantitative analytical research with a Cross Sectional Study approach. The research population were 1134 inpatient medical records (MR). The sample used were 92 MRs using the systematic sampling technique. The independent variable was the completeness of medical information and the dependent variable was the accuracy of the disease diagnosis code. Data were collected through observation in the coding section and used checklist sheets. The outcome showed the completeness of medical information was 67% and the accuracy of disease diagnosis codes was 72%. The Chi Square test showed a relationship between the completeness of medical information and the accuracy of disease diagnosis codes in the inpatient MR at the University of Muhammadiyah Malang Hospital (p-value < 0.05). It is necessary to evaluate the completeness of filling in medical information in MR continuously to improve the accuracy of disease diagnosis codes.